Are Past Adverse Pregnancy Outcomes Associated with Maternal Anxiety and Depressive Symptoms in a Sample of Currently Pregnant Women? - Abajobir, A.; Alati, Rosa; Kisely, S.; Najman, J. (2017)
Background: There has been a great deal of concern about the mental health of women whose pregnancies involve miscarriage, termination of a pregnancy (ToP), child death or where a child has been given up for adoption. Despite this concern there has been remarkably little population-based research which has addressed the long-term consequences of pregnancy loss and child death. This study investigated the maternal mental health consequences of women whose pregnancies involve miscarriage, ToP, child death or where a child has been given up for adoption at two different time points, adjusting for socio-demographic characteristics and baseline mental health.Methods: The Mater-University of Queensland Study of Pregnancy is a prospective pre-birth cohort study. Women were recruited early in pregnancy over the period 1981 to 1983 at their first antenatal clinic visit (FCV). Women were interviewed again at the 14-year follow-up. Data from 4403 mothers were analysed using maternal reports of a prior history of giving a child up for adoption, miscarriage, ToP, and neonatal, infant and/or child deaths. Symptoms of maternal anxiety and depression were measured at FCV and the 14-year follow-up using the Delusions-Symptoms-States Inventory. We carried out logistic regression analysis using Stata 13. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to display the findings.Results: A prior miscarriage was associated with anxiety (adjusted OR (AOR) = 1.30; 95% CI: 1.10-1.66) and depressive (AOR = 1.70; 95% CI: 1.21-2.39) symptoms at the 14-year follow-up. Having had a neonatal, infant and/or child deaths was associated with symptoms of depression at 14-year follow-up (AOR = 2.12; 95% CI: 1.06-4.25).Conclusion: The period after a child loss which involves a new pregnancy may be associated with relatively good mental health despite the fact that some mothers have experienced previous adverse pregnancy outcomes.